Utility of the Neutrophil to Lymphocyte Ratio for Predicting Mortality in Pleural Empyema - A Retrospective Study - Dimitrov, Evgeni; Valchev, Daniel; Minkov, Georgi; Enchev, Emil; Yovtchev, Yovcho (Current Respiratory Medicine Reviews, 2025)
IntroductionThe prognostic qualities of the hematological biomarker neutrophil to lymphocyte ratio (NLR) have not yet been evaluated in pleural empyema. Therefore, we aimed to find if NLR can predict adverse outcome in such clinical setting.MethodsRetrospectively we studied 84 patients with pleural empyema who were operated in emergency setting in a clinic of thoracic surgery of an academic hospital over a 34-month period (01.2021- 10.2023). To assess the prognostic performance of NLR we used the area under the receiver operating characteristics (AUROC) curves.ResultsOf a total of 84 patients, nine (10.7%) died. Using ROC Curve analysis we found that NLR has an excellent prognostic ability and outperformed systemic immune inflammation index (SII), platelet to lymphocyte ratio (PLR), quick- sequential organ failure (qSOFA) score and systemic inflammation response syndrome (SIRS) (AUROC = 0.904 vs 0.782 vs 0.749 vs 0.747 vs 0.676, respectively) in outcome prediction. An optimal threshold NLR > 9.88 x 109/L for prognostication of death was identified with a sensitivity of 85.7% and a specificity of 83.6%.ConclusionIn pleural empyema the neutrophil to lymphocyte ratio demonstrates excellent ability to predict the unfavorable outcome.
Keywords: pleural infection